Markedness Effects in the Semiotactics of the Hieratic Markers of the Stone Tablets in the Christian Sacrosphere - Małgorzata Haładewicz-Grzelak (Półrocznik Językoznawczy Tertium, 2024)
The present article inscribes itself in the realm of the investigation of visual hieratic textuality. In the article, I use semiotactics as the methodology developed on the basis of contemporary phonology (in particular, (mor)phonotactics, e. g. Dressler and Dziubalska-Kołaczyk 2006 inter alia) to examine salient asymmetries as markedness phenomena operating on a hieratic marker active both in the Judaic denomination and in Christianity ‒ the Stone Tablets. In particular, I focus on the semiotactic reflection of the markedness effects related to the presence of the analysed marker in Catholic churches. I establish several implicational cooccurrence restrictions and arrive at establishing several primes in the nano-structure of a hieratic sign. The basis for the analysis is the digital documentation of the representation of the Stone Tablets in Christian churches which I collected in various European countries in the years 2010‒2022.